Acoustic Telemetry Reveals the Complex Nature of Mixed‐Stock Fishing in Canada's Largest Arctic Char Commercial Fishery. (1st September 2022) - Harris, Les. N.; Yurkowski, David J.; Malley, Brendan K.; Jones, Samantha F.; Else, Brent G.T.; Tallman, Ross F.; Fisk, Aaron T.; Moore, Jean‐Sébastien
Abstract: Climate change is having a myriad of effects on Arctic ecosystems, yet understanding how these changes will influence the spatiotemporal dynamics of harvest in northern commercial fisheries remains unclear. Furthermore, stock mixing continues to complicate fisheries management in Arctic Canada, especially for anadromous stocks, but data on the extent and degree of stock mixing for the majority of northern fisheries are scarce. Here, we used a multiyear (2015–2019) acoustic telemetry data set to test the utility of acoustic telemetry as a potential tool for inferring stock mixing in the Arctic Char Salvelinus alpinus commercial fishery in Cambridge Bay (Nunavut). We also assessed the effect of annual variation in environmental variables (river breakup and marine ice conditions) on the potential contribution of discrete stocks to commercial harvest at several fisheries. We found that stock mixing during the commercial harvest is common in both marine and freshwater fisheries during the summer/open‐water season, with virtually all stocks potentially being susceptible to harvest at any given commercial fishery. Additionally, in some fisheries, the vulnerability of different stocks to harvest was influenced by annual differences in marine ice and river breakup conditions. We discuss options for fisheries management, including a potential quota‐transfer system, and highlight how changing environmental and climatic conditions may have an effect on the commercial harvest of Arctic Char in the region. Overall, the results of this study demonstrate the utility of acoustic telemetry for informing mixed‐stock fisheries while highlighting the complex and pervasive nature of stock mixing in Canada's largest Arctic Char commercial fishery.